Color image encryption algorithm based on Fisher-Yates scrambling and DNA subsequence operation - Wang, Xingyuan; Su, Yining; Liu, Lin; Zhang, Hao; Di, Shuhong (The Visual computer, 2023)
In this paper, a color image encryption algorithm based on Fisher-Yates scrambling and DNA subsequence operation (elongation operation, truncation operation, deletion operation, insertion arithmetic) is proposed. Firstly, the three-dimensional color image is transformed into two-dimensional gray image, and the chaotic sequence generated by Chen system and Fisher-Yates scrambling method is used to scramble the plaintext images of R, G and B channels. Secondly, the three channel images of the scrambled plaintext image are transformed into three DNA sequence matrixes by using the DNA coding rules, and then the three DNA sequence matrixes are manipulated by using DNA subsequence operation and DNA addition, subtraction and XOR operation to destroy the scrambled plaintext information. Finally, the color encrypted image is obtained by using the DNA decoding rule. Experimental results and security analysis demonstrate that our encryption algorithm has good performance and may resist against various typical attacks.